The role of the bone morphogenetic proteins in leukaemic stem cell persistence. (11th August 2014) - Toofan, Parto; Irvine, David; Hopcroft, Lisa; Copland, Mhairi; Wheadon, Helen
Abstract : CML (chronic myeloid leukaemia) is characterized by the presence of the oncogenic tyrosine kinase fusion protein BCR (breakpoint cluster region)–Abl, responsible for driving the disease. Current TKI (tyrosine kinase inhibitor) therapies effectively inhibit BCR–Abl to control CML in the majority of patients, but do not eliminate the LSC (leukaemic stem cell) population, which becomes quiescent following treatment. Patients require long-term treatment to sustain remission; alternative strategies are therefore required, either alone or in combination with TKIs to eliminate the LSCs and provide a cure. The embryonic morphogenetic pathways play a key role in haemopoiesis with recent evidence suggesting LSCs are more dependent on these signals following chemotherapy than normal HSCs (haemopoietic stem cells). Recent evidence in the literature and from our group has revealed that the BMP (bone morphogenetic protein) pathway is differentially expressed in CML patients compared with normal donors. In the present review, we explore the role that BMP signalling plays in oesteoblast differentiation, HSC maintenance and the implication of altered BMP signalling on LSC persistence in the BM (bone marrow) niche. Overall, we highlight the BMP pathway as a potential target for developing LSC-directed therapies in CML in the future.